2009
DOI: 10.1074/jbc.m109.037614
|View full text |Cite
|
Sign up to set email alerts
|

Ostreococcus tauri ADP-glucose Pyrophosphorylase Reveals Alternative Paths for the Evolution of Subunit Roles

Abstract: ADP-glucose pyrophosphorylase controls starch synthesis in plants and is an interesting case to study the evolution and differentiation of roles in heteromeric enzymes. It includes two homologous subunits, small (S) and large (L), that originated from a common photosynthetic eukaryotic ancestor. In present day organisms, these subunits became complementary after loss of certain roles in a process described as subfunctionalization. For instance, the potato tuber enzyme has a noncatalytic L subunit that compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 55 publications
2
44
0
Order By: Relevance
“…To explore this hypothesis more narrowly, based on literature and sequence databases (Uniprot, JGI), we checked whether enzymes of the starch metabolic pathway in O. tauri contain the target sequences reported as responsible for the redox-related modifications for plant species, namely, for AGPase, GWD and β-amylase enzymes [16-18]. Our sequence analysis revealed that in addition to already published results for O. tauri [25] and C. reinhardtii [24], neither AGPases of O. lucimarinus nor both Micromonas species contain the redox-target sequences (Figure 6). The same is true for another known redox regulated enzyme, GWD, which is believed to initiate the starch mobilization process.…”
Section: Discussionmentioning
confidence: 97%
“…To explore this hypothesis more narrowly, based on literature and sequence databases (Uniprot, JGI), we checked whether enzymes of the starch metabolic pathway in O. tauri contain the target sequences reported as responsible for the redox-related modifications for plant species, namely, for AGPase, GWD and β-amylase enzymes [16-18]. Our sequence analysis revealed that in addition to already published results for O. tauri [25] and C. reinhardtii [24], neither AGPases of O. lucimarinus nor both Micromonas species contain the redox-target sequences (Figure 6). The same is true for another known redox regulated enzyme, GWD, which is believed to initiate the starch mobilization process.…”
Section: Discussionmentioning
confidence: 97%
“…Site-directed mutagenesis was performed by PCR overlap extension as previously described using Phusion DNA polymerase (30,31). The plasmid encoding the N. europaea sucrose synthase (pNESS2) was used as a template for mutagenesis.…”
Section: Methodsmentioning
confidence: 99%
“…It is believed that the ancestral enzyme may have been a bacterial subunit with both catalytic and regulatory functions [2]. Based on the roles of different S and L subunits from plants, it seems that after gene duplication ADP-Glc PPase has undergone a subfunctionalization process in which each copy adopted complementary roles [4]. The interaction between the product of these gene copies is now necessary to maintain the same overall set of functions of the common ancestor [4].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the roles of different S and L subunits from plants, it seems that after gene duplication ADP-Glc PPase has undergone a subfunctionalization process in which each copy adopted complementary roles [4]. The interaction between the product of these gene copies is now necessary to maintain the same overall set of functions of the common ancestor [4]. This duplication and divergence increased the sequence landscape and enabled ADP-Glc PPase to evolve towards more complex regulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation